Menstimulasi Perkembangan Sensorik dan Motorik Anak dengan Kebutuhan Khusus - Meylani D. Wowor; Ignatia Y. Rembet; Risca Manoppo; Priscila Assa (STIKES Columbia Asia Medan, 2024)
Child development problems are also related to learning and education problems. In the learning process, a combination of psychosocioemotional, psychomotor skills, medical, and language relationships is needed. These four things are the main keys or gateways to a bright future, especially for children who have learning problems. This study discusses learning media used to train sensory and motor skills of children with special needs using the socialization and demonstration method at St. Anna Tomohon Special School. The phenomenon found at St. Anna Tomohon Special School is that they have problems with sensory, motoric, and learning processes. This results in disruption of the child's physical development. The purpose of creating a sensory playmat is to train good coordination between the five senses and movement to the stimulation received. Located at St. Anna Tomohon Special School, with 21 participants in the activity. Various reactions were found when children demonstrated which were tested by imitating and following games such as acceptance and rejection